Integrated Proteome Analysis Device for Fast Single-Cell Protein Profiling - Shao, Xi; Wang, Xuantang; Guan, Sheng; Lin, Haizhu; Yan, Guoquan; Gao, Mingxia; Deng, Chunhui; Zhang, Xiangmin (Analytical chemistry (Washington), 2018)
In our previous work, we have demonstrated an integrated proteome analysis device (iPAD-100) to analyze proteomes from 100 cells. In this work, for the first time, a novel integrated device for single-cell analysis (iPAD-1) was developed to profile proteins in a single cell within 1 h. In the iPAD-1, a selected single cell was directly sucked into a 22 μm i.d. capillary. Then the cell lysis and protein digestion were simultaneously accomplished in the capillary in a 2 nL volume, which could prevent protein loss and excessive dilution. Digestion was accelerated by using elevated temperature with ultrasonication. The whole time of cell treatment was 30 min. After that, single-cell digest peptides were transferred into an LC column directly through a true zero dead volume union, to minimize protein transfer loss. A homemade 22 μm i.d. nano-LC packing column with 3 μm i.d. ESI tip was used in the device to achieve ultrasensitive detection. A 30 min elution program was applied to analysis of the single-cell proteome. Therefore, the total time needed for a single-cell analysis was only 1 h. In an analysis of 10 single HeLa cells, a maximum of 328 proteins were identified in one cell by using an Orbitrap Fusion Tribrid MS instrument, and the detection limit was estimated at around 1.7–170 zmol. Such a sensitivity of the iPAD-1 was ∼120-fold higher than that of our previously developed iPAD-100 system. Prominent cellular heterogeneity in protein expressive profiling was observed. Furthermore, we roughly estimated the phases of the cell cycle of tested HeLa cells by the amount of core histone proteins.